DIFFERENTIAL SCANNING CALORIMETRY AT CHARGE-DENSITY-WAVE TRANSITIONS - WANG, YQ; CHUNG, M; ONEAL, TN; BRILL, JW (ELSEVIER SCIENCE SA LAUSANNE, 1992)
We examined the use of differential scanning calorimetry (DSC) to measure the specific heat anomalies at second-order charge-density-wave transitions in blue bronze (K0.3MoO3), NbSe3 and TaS3. Samples of different morphologies were investigated to examine possible effects of different thermal time constants; results were generally independent of morphology. For blue bronze, an anomaly DELTA-c(p) = 0.16R was found at its 180 K transition; for NbSe3, DELTA-c(p) = 0.06R at 142 K, and for TaS3, DELTA-c(p) < 0.03R at 220 K. Our results demonstrate the practicality of using DSC for the quantitative measurement of small specific heat anomalies (greater-than-or-similar-to 0.2%) in synthetic metals.
Keywords: BLUE BRONZE K0.3MOO3; PEIERLS TRANSITION; THERMAL-CONDUCTIVITY; PHASE-TRANSITIONS; HEAT ANOMALIES; NBSE3; TAS3; THERMODYNAMICS